Associations between Sports Videogames and Physical Activity in Children - Ng Kwok; Kaskinen Ari-Pekka; Katila Rauli; Koski Pasi; Karhulahti Veli-Matti (SCIENDO, 2022)
Objective: The aim of the study was to examine the associations of sports video gaming behaviour in the sociological concept of Physical Activity Relationships (PAR) and to see if sports video gaming differs by gender.
Methods: A convenience sample of children between 11-12 years of age (n = 114) from three Finnish regions completed a questionnaire on perceptions of their video gaming and physical activity habits. Differences by gender were tested by contingency tables, and blockwise binary logistic regressions were used to examine the strength of association with physical activity behaviour in PAR.
Results: Almost all girls had low importance to video gaming and over two thirds (71%) reported their frequency in sports video gaming was less than monthly. Sports video gaming was positively associated with physical activity behaviours (OR = 3.4, CI =1.3-9.0), but when combined with perceived physical activity importance and spectating in sports, the association was no longer statistically significant. There were no differences in gender for non-sports video gaming.
Conclusions: For children who partake in sports video games, the activity can be an integral part of their overall PAR. These preliminary results require further exploring prior to drawing societal implications or sports video games or applying them for intervention to promote physical activity.